(3eHGOF GdGbJUGO GdSjGSj (B:s (3GdGbJUGO GdeGdj (B/s - (3OhjOGQ, eMeOs ((3GdLRGFQ(B: s (3GdeDSSI GdhWfjI ddafhf GdeWHYjI(B, s, 2014)
(3COhGJ GdSjGSI GdeGdjI(B:(3GdfXQjI GdYGeI ddeGdjI GdYGeI, fXQjI GdGfaGb GdYGe,fXQjI GdGjQGO GdYGe(B:(3fXQI TGedI, fXQjI GdGjQGO GdYGe fXQjI GdVQjHI, fXQjI GdGjQGO GdYGe(B:(3GdfXGe GdVQjHj, fXQjI GdGjQGO GdYGe fXQjI GdbQV GdYGe, GdehGRfI GdYGeI ddOhdI, GdSjGSI GdeGdjI, ecGf JjGQGJ GdeGdjI GdYGeI ef JjGQGJ GdONd Gdbhej, GdSjGSGJ GdeGdjI aj GdGbJUGO GdQCSeGdj GdeJbOe, GdSjGSI GdeGdjI hGdGbJUGO GdeJNdas
(3eQGLY U(B.685((3GbJfGAGJ (B2014 01(3f(B)s
Keywords: (3GdEbJUGO GdQCSeGdjs; (3GdEbJUGO GdSjGSjs; (3GdSjGSI GdeGdjIs